Determination of the optimal frequency and duration of micro-spray patterns for high-temperature environment tomatoes based on the Fuzzy Borda model - Run Xue; Chuan Zhang; Haofang Yan; Kinde Negessa Disasa; Imran Ali Lakhiar; Muhammad Akhlaq; Muhammad Usman Hameed; Jun Li; Jiangtao Ren; Shuaishuai Deng; Biyu Wang; Rongxuan Bao (Agricultural Water Management)
High summer temperatures have a significant impact on the yield reduction and quality of greenhouse crops. Micro-spray has been increasingly utilized in greenhouses to enhance crop productivity and quality. Nevertheless, micro-spray applications' optimal frequency and duration vary depending on the specific temperature conditions to enhance the fruit quality. Thus, this study implemented different micro-spray frequencies, F1 (once per hour) and F2 (twice per hour), and durations, D1 (1 minute), D2 (2 minutes from 11:00–13:00 and 1 minute during other times) and D3 (2 minutes) treatments to study the impact of micro-spray durations and frequencies on tomato chlorophyll fluorescence parameters, growth indicators, and fruit quality, and constructed the Fuzzy Borda combination evaluation (FB) model to obtain the optimal micro-spray treatments. The results showed that micro-spray effectively improved tomato growth indicators and fruit quality. The micro-spray restored part of the photosynthetic mechanism of tomato that was stopped due to high temperature and reduced the photoprotective mechanism, actively dissipating excess energy into heat. F2 had a better effect on improving plant height, LAI, and SPAD than F1. All micro-spray treatments increased yield but decreased WPc in all of them. Meanwhile, the yield was significantly and positively correlated with LAI and SPAD. Thus, yield could be predicted from LAI and SPAD. In the FB model, F1D3 and F2D1 treatments had the highest scores and rankings of tomatoes, which can be applied to protect tomatoes against heat damage and maximize the economic benefits. Meanwhile, TOPSIS, RSR, or VIKOR can be used to quickly assess tomatoes' superiority or inferiority under different treatments because they had the highest correlation with the FB. In future studies, we need to further investigate the functional distribution of mist and the process of mist changes, which could help us better understand the mechanism of micro-spray.